Combined exposure to protons and 56Fe leads to overexpression of Il13 and reactivation of repetitive elements in the mouse lung. (November 2015) - Nzabarushimana, Etienne; Prior, Sara; Miousse, Isabelle R.; Pathak, Rupak; Allen, Antiño R.; Latendresse, John; Olsen, Reid H.J.; Raber, Jacob; Hauer-Jensen, Martin; Nelson, Gregory A.; Koturbash, Igor
Abstract: Interest in deep space exploration underlines the needs to investigate the effects of exposure to combined sources of space radiation. The lung is a target organ for radiation, and exposure to protons and heavy ions as radiation sources may lead to the development of degenerative disease and cancer. In this study, we evaluated the pro-fibrotic and epigenetic effects of exposure to protons (150 MeV/nucleon, 0.1 Gy) and heavy iron ions ( 56 Fe, 600 MeV/nucleon, 0.5 Gy) alone or in combination (protons on Day 1 and 56 Fe on Day 2) in C57BL/6 male mice 4 weeks after irradiation. Exposure to 56 Fe, proton or in combination, did not result in histopathological changes in the murine lung. At the same time, combined exposure to protons and 56 Fe resulted in pronounced molecular alterations in comparison with either source of radiation alone. Specifically, we observed a substantial increase in the expression of cytokine Il 13, loss of expression of DNA methyltransferase Dnmt1, and reactivation of LINE-1, SINE B1 retrotransposons, and major and minor satellites. Given the deleterious potential of the observed effects that may lead to development of chronic lung injury, pulmonary fibrosis, and cancer, future studies devoted to the investigation of the long-term effects of combined exposures to proton and heavy ions are clearly needed.